Effect of perforation shape and porosity on effective thermal conductivity of matrix heat exchanger plates. (5th August 2016) - Navaneethakrishnan, P.; Krishnakumar, K.; John, Anish K.
Highlights: The effective thermal conductivity (keff ) of the perforated plates is determined. Porosity and perforation geometry are the two influencing parameters. The correlations connecting keff and porosity are determined. New parameter called perforation coefficient (dpc ) is coined to account for geometry. A bi – variable correlation is obtained. Abstract: The effective thermal conductivity of a matrix heat exchanger plate is used to determine the heat transfer characteristics of the matrix exchanger in transient testing methods. In this paper, the influence of two parameters namely porosity, which is an indication of the void space and perforation shape, which is the geometry of the void, on effective thermal conductivity is analysed numerically and experimentally. The perforated copper plates of square, rhomboidal, rectangular and circular shapes of different porosities are used. A new parameter called perforation coefficient which generalises the different perforation shapes is coined. Correlations are developed using regression analysis to understand the effect of these parameters on effective thermal conductivity.